2017
DOI: 10.1161/circheartfailure.117.003874
|View full text |Cite|
|
Sign up to set email alerts
|

Symptom Diary Use and Improved Survival for Patients With Heart Failure

Abstract: Background Attention to symptoms of weight gain and dyspnea are central tenets of patient education in heart failure (HF). However, it is not known whether diary use improves patient outcomes. The aims of the study were to compare mortality among rural patients with HF who completed versus did not complete a daily diary of weight and symptom self-assessment and to identify predictors of diary use. Methods and Results This is a secondary analysis of a 3-arm randomized controlled trial on HF education of self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 46 publications
(52 reference statements)
0
22
0
2
Order By: Relevance
“…App-related DBT studies have shown potential in allowing users to learn and practice a wide range of skills; however, major barriers include app navigation challenges and difficulties understanding interventions without prior DBT exposure or clinical support [ 41 , 42 ]. Nonetheless, increasing symptom awareness and tracking, via diary cards, have been shown to be helpful for various conditions, including those in jeopardy of heart failure, chronic bronchitis, and pulmonary diseases [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…App-related DBT studies have shown potential in allowing users to learn and practice a wide range of skills; however, major barriers include app navigation challenges and difficulties understanding interventions without prior DBT exposure or clinical support [ 41 , 42 ]. Nonetheless, increasing symptom awareness and tracking, via diary cards, have been shown to be helpful for various conditions, including those in jeopardy of heart failure, chronic bronchitis, and pulmonary diseases [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Education for patients and family members. 16,[55][56][57] Patient, relatives and caregivers empowerment is indispensable to achieve a good therapeutic adherence and to optimize the results of treatment. All educational measures aimed at improving disease awareness, drug management, recognition of alarming data, should be considered within an HF educational program.…”
Section: P S Y C H O L O G I C a L E V A L U A T I O N A N Dmentioning
confidence: 99%
“…Diaries to support the patients have been used in different patients' groups (Jimoh, Bunn, & Hooper, 2015; Park et al., 2017; Ullman et al., 2015) and seem to have increase self‐reliance and self‐management in some patient populations (Van Woensel, Roy, Abidi, & Abidi, 2015). Furthermore, diaries have been used in the pre‐transplant period of candidates for lung transplantation to monitor early detection of clinical problems (Mullan, Snyder, Lindgren, Finkelstein, & Hertz, 2003).…”
Section: Introductionmentioning
confidence: 99%